EFECTO INHIBITORIO DE LA PROGESTERONA SOBRE EL DESARROLLO DE LA ONDA FOLICULAR EN LLAMAS - Santiani A., Alexei (2002)
The effect of the exogenous progesterone (P4) on the development of follicular waves in llamas was studied in twenty-five females. According to dose and regimen for P 4 administration, animals were allocated to 5 groups (n=5): 00 (control group ), G 1 (30 mg P /day for 2 days); G2 (30 mg P/day for 4 days); G3 (50 mg P /day for 2 days) and G4 (50 mg P /da y for 4 days ). Development of dominant ():. 7 mm) and subordinated follicles (>3 mm and < 7 mm) were monitored daily by transrectal ultrasonography. The minimun size reachedbythedorninantfollicleingroupsGl (4.6±0.9mm), G3(5.1±1.5 mm) andG4(5.3 ± 1.6 mm) were smaller (P< 0.05) than group 00 (8.5 ± 1.0 mm). The whole follicular regression of the dominant follicle in groups G 1 (5.5 ± 2.0 mm), G2 (5.9 ± 1.4 mm) and G3 (5.3 ± 3. 3 mm) were larger (P< 0.05) than group 00 (0.9 ± 1.4 mm). The number of subordinated follicles hada significative increase (P< 0.05) in groups G 1 and G4, on days 2 and 3 in relation to days 7 and 8 post-treatment. Results demonstrate that exogenous progesterone inhibits the development of the dominant and subordinate follicles in lla-mas during treatment days; however, immediately after the end of the treatment, the · number of subordinate follicles increases, due to the regression of the dominant follicle in order to allow the emergence of a new follicular wave.